Consensus among musculoskeletal experts for the management of patients with headache by physiotherapists? A delphi study. (April 2021) - De Pauw, Robby; Dewitte, Vincent; de Hertogh, Willem; Cnockaert, Elise; Chys, Marjolein; Cagnie, Barbara
Abstract: Background: Though a large amount of research on the management of headache has been conducted, the clinical effectiveness of these treatments remains unclear. Objectives: To reach consensus among international musculoskeletal experts on what the most appropriate management is in patients that suffer from headache. Design: Expert group and Delphi-study. Methods: A total of 11 experts participated in the expert panel groups, where the role of physiotherapy in the management of headache was discussed. Afterwards, 14 of the initial 25 participants in the field of headache completed the whole Delphi study, which was conducted over 4 rounds. The first round aimed to identify clinical indicators and treatments that are useful in patients with headache. These questions were then categorized and ranked during the second, third, and fourth rounds. Consensual agreement was set at ≥ 80%. Results: After the final round, 9 interventions were rated as useful by the participants. In the final extra round, 14 clinical indicators were retrieved as important to decide whether or not to start one of the consensual treatments. The top 3 management strategies were (1) upper cervical spine mobilisations in cervivogenic headache, (2) active mobilisation exercises of the cervical spine in cervivogenic headache, and (3) lifestyle advice in tension-type headache and migraine. Conclusion: International experts agreed that most scientifically established effective treatments are useful in cervicogenic headache. Consensual agreement on treatments for migraine and tension-type headache were only reached for specific treatments. Their recommendations provide a framework for further research and the clinical management of headache. Highlights: Mobilisation exercises & ergonomic training are useful for cervicogenic headache. Tension-type headache can best be treated with advice, and trigger point techniques. This study emphasizes the usefulness of clinical indicators in clinical practice.